2013
DOI: 10.1111/j.2047-6310.2012.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between perinatal factors and adiponectin and leptin in 9‐year‐old Mexican–American children

Abstract: Objectives To 1) determine whether perinatal factors (including maternal anthropometry and nutrition and early life growth measures) are associated with adiponectin and leptin levels in 9-year-old children, and 2) assess relationships between adiponectin, leptin and concurrent lipid profile in these children. Methods We measured plasma adiponectin and leptin for 146 mother - 9-year-old child pairs from the ongoing longitudinal birth cohort followed by the Center for the Health Assessment of Mothers and Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…We observed that maternal PC scores at post-supplementation were positively associated with child PC scores at 9-12 years. Previous studies showed that maternal leptin concentration was correlated with children’s leptin concentration in cord blood [23,48] and serum of 9-years old children [49]. Postpartum maternal biomarkers may be associated with child biomarkers through breast milk, in agreement with a previous study that reported a correlation between leptin concentration in breast milk with its concentration in maternal serum and infant’s weight gain [50].…”
Section: Discussionsupporting
confidence: 87%
“…We observed that maternal PC scores at post-supplementation were positively associated with child PC scores at 9-12 years. Previous studies showed that maternal leptin concentration was correlated with children’s leptin concentration in cord blood [23,48] and serum of 9-years old children [49]. Postpartum maternal biomarkers may be associated with child biomarkers through breast milk, in agreement with a previous study that reported a correlation between leptin concentration in breast milk with its concentration in maternal serum and infant’s weight gain [50].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies showed that maternal leptin concentration was correlated with child leptin concentration in cord blood [23,51] and serum of 9-years old children [52]. Postpartum maternal biomarkers may be associated with child biomarkers through breast milk, in agreement with a previous study that reported a correlation between leptin concentration in breast milk with its concentration in maternal serum and infant weight gain [53].…”
Section: Plos Onesupporting
confidence: 89%
“…Plasma adipokines were measured using enzyme-linked immunoassay (ELISA) RayBiotech Human Adiponectin and Human Leptin kits (RayBiotech Inc., Norcross, GA, USA). The protocol developed by the manufacturer was used, with some previously described modifications (37) to increase precision for assessment in children: (i) the standard curve for adiponectin was narrowed in order to obtain better resolution at smaller readings, (ii) the standard curve for leptin was broadened, and (iii) plasma samples in the leptin analysis were more diluted. Final dilutions for the RayBio Human Leptin ELISA and the Human Acrp30 ELISA were 1:70 and 1:30,000, respectively.…”
Section: Methodsmentioning
confidence: 99%